A Comparative Analysis of Perca fluviatilis Population Dynamics From Two Lakes in New Zealand - Banda, Fiona (Auckland University of Technology, 2014)
This thesis comparatively examined the population dynamics of European Perca fluviatilis populations from Warkworth Quarry Lake and Lake Rototoa. A total of 206 fish samples from Warkworth Quarry Lake and 99 fish samples from Lake Rototoa were histologically analyzed and sagittal otoliths examined to obtain estimates of reproductive, age and growth parameters. Diet was analyzed through visual assessment of stomach contents while catch per unit effort provided an index of relative abundance of populations. Age and size structure analysis showed the dominance of females in the structure of both populations while the maximum age in Warkworth Quarry Lake and Lake Rototoa populations were 6+ and 7+ respectively. Growth rate was rapid in the first year in both populations while high growth rates were achieved in subsequent years in Lake Rototoa population. There were no significant differences (p<0.001) in expected size-at-age between males and females of the two populations. There were differences in sex ratio between the populations and this was influenced by location, population growth rate and sampling gear. Sexual maturity was attained between year 1 and 2 and temperature was the main abiotic factor affecting the reproductive biology of Perca fluviatilis. This was reflected in the height of gonadosomatic index occurring during the winter months of New Zealand and an extended vitellogenic period of 9 months experienced by both populations. Additional reproductive anomalies present in both populations were the presence of atretic eggs, asynchronous egg cell development, lack of resorbing egg cells, scarce presence of post-ovulatory follicles and presence of individuals with gonadal stages associated with spawning outside the documented spring spawning season in New Zealand. Diets of fish 50 – 180 mm SL comprised of small aquatic invertebrates. Fish >180mm SL in Warkworth Quarry Lake were cannibalistic, whereas in Lake Rototoa they preyed almost exclusively on Paranephrops planifrons. The results indicate the impact of Perca fluviatilis on native species and an adaptation to New Zealand waters through variation in growth patterns, feeding patterns and reproductive traits. Although this study provides tentative evidence of an extended spawning season, it is conclusive that Perca fluviatilis in New Zealand have life traits whose biological plasticity is attributed to latitudinal gradient.
Keywords: Perca fluviatilis; Otoliths; Histology; New Zealand; Reproductive biology; Age; Growth; Diet; Relative abundance